Review on Dissolved Organic Carbon and Particulate Organic Carbon in Marine Environment - Radha Karuna Kumari; P. M. Mohan (Marine Science Department Diponegoro University, 2018)
Quantification the Dissolved and Particulate organic carbon in marine waters is an essential step towards ecosystem modeling and understanding carbon sequestration processes. A detailed view of estimated and recorded carbon concentration from Arctic to Antarctic is the prime goal of this review. This review compiles some of the important research work carried out in quantifying the organic carbon available in off shore and open waters and in coral reef environment. The cited literatures were collected, grouped and carefully analyzed to give a comprehensive view on current status of marine environment with regard to distribution of dissolved and particulate organic carbon. Keywords: DOC, POC, continental shelf waters, open sea waters, coral reef environment.